Deletion of Mgr2p Affects the Gating Behavior of the TIM23 Complex - Mirzalieva, Oygul; Jeon, Shinhye; Damri, Kevin; Hartke, Ruth; Drwesh, Layla; Demishtein-Zohary, Keren; Azem, Abdussalam; Dunn, Cory D.; Peixoto, Pablo M. (Frontiers in Physiology, 2019)
The TIM23 complex is a hub for translocation of preproteins into or across the mitochondrial inner membrane. This dual sorting mechanism is currently being investigated, and in yeast it seems to be regulated by a recently discovered subunit, the Mgr2 protein. Deletion of Mgr2p has been found to delay protein translocation into the matrix and accumulation in the inner membrane. This result and other findings suggested that Mgr2p controls the lateral release of inner membrane proteins harboring a stop-transfer signal that follows an N-terminal acid signal. However, the mechanism of lateral release is unknown. Here, we used patch clamp electrophysiology to investigate the role of Mgr2 on the channel activity of TIM23. Deletion of Mgr2p decreased normal channel frequency and increased occurrence of a residual TIM23 activity. The residual channel lacked gating transitions but remained sensitive to synthetic import signal peptides. Similarly, a G145L mutation in Tim23p displaced Mgr2p from the import complex leading to gating impairment. These results suggest that Mgr2p regulates the gating behavior of the TIM23 channel.